2017
DOI: 10.3390/jfb8040049
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Craniomaxillofacial Bone Defects Using Tissue-Engineering Strategies with Injectable and Non-Injectable Scaffolds

Abstract: Engineering craniofacial bone tissues is challenging due to their complex structures. Current standard autografts and allografts have many drawbacks for craniofacial bone tissue reconstruction; including donor site morbidity and the ability to reinstate the aesthetic characteristics of the host tissue. To overcome these problems; tissue engineering and regenerative medicine strategies have been developed as a potential way to reconstruct damaged bone tissue. Different types of new biomaterials; including natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 122 publications
0
46
0
Order By: Relevance
“…Engineering the maxillofacial bones is challenging due to the presence of complex physiological structures such as sensory organs, facial skeletal features, cartilage and blood vessels. Moreover, clinicians have to control bacterial contamination in highly susceptible areas, including the oral and nasal regions 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineering the maxillofacial bones is challenging due to the presence of complex physiological structures such as sensory organs, facial skeletal features, cartilage and blood vessels. Moreover, clinicians have to control bacterial contamination in highly susceptible areas, including the oral and nasal regions 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The regeneration of facial skeletal tissues must consider ways to ensure the restoration of aesthetics. Additionally, reconstruction should give sufficient mechanical strength and support movement due to speech and masticatory functions 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The success of this approach has resulted in a range of popular, commercially available, hydroxyapatite powders, cements, and granules including: Bio‐Oss (Geistlich Ltd., Switzerland) and Fisiograft Bone (Ghimas S.p.A, Italy). In addition, hybridization of inorganic materials with polymers and/or growth factors has been explored as injectable composite materials for craniomaxillofacial bone tissue engineering 12. Similarly, membranes made from synthetic ( exe .…”
Section: Introductionmentioning
confidence: 99%
“…Popular stem cell used in dental tissue engineering is the periodontal ligament stem cells (PDLSC) which is extracted from discarded teeth and has the potential to generate the cementum and periodontal ligament-like structure. Studies have shown that these stem cells also have the potential to develop into the osteogenic and adipogenic tissues in vitro, opening up multiple opportunities for tissue engineering from dental-derived stem cells [46].…”
Section: Stem Cells In the Scaffoldsmentioning
confidence: 99%